HIIT and Aloe Vera Supplementation Improve METRNL Levels, Reduce Oxidative Stress, and Enhance Antioxidant Status in Men With Type 2 Diabetes (Baltic Journal of Sport and Health Sciences, 2026)
Background: Hyperglycaemia, oxidative stress, and chronic inflammation play critical roles in the pathogenesis and progression of type 2 diabetes mellitus (T2DM). This study aimed to evaluate the effects of high-intensity interval training (HIIT), Aloe vera supplementation, and their combination on Meteorin-like (METRNL) protein levels, oxidative stress markers, and antioxidant status in men with T2DM.Methods: In this semi-experimental study, 44 men with T2DM (aged 25–40 years) were randomly assigned to one of four groups (n = 11 per group): (1) HIIT, (2) Aloe vera supplementation, (3) HIIT + Aloe vera, and (4) Control. The HIIT protocol was conducted three times per week for 12 weeks. Participants in the Aloe vera groups received two 100 mg capsules of Aloe vera gel powder daily, one in the morning upon waking and one after dinner. Fasting blood samples were collected before and after the intervention. Data were analysed using two-way repeated-measures ANOVA, paired-sample t-tests, and Bonferroni post hoc comparisons.Results: HIIT, Aloe vera supplementation, and their combination significantly increased METRNL, glutathione peroxidase (GPx), superoxide dismutase (SOD), and total antioxidant capacity (TAC), while significantly reducing malondialdehyde (MDA) levels compared with the control group (p < 0.001). The HIIT + Aloe vera group demonstrated the greatest improvements across all markers, followed by HIIT alone, while Aloe vera alone produced moderate but significant effects.Conclusion: Both HIIT and Aloe vera supplementation independently improved antioxidant defence and reduced oxidative stress in men with T2DM, however, their combination elicited the most pronounced benefits, suggesting a synergistic effect. These findings support integrating structured exercise with phototherapeutic supplementation as a complementary strategy to enhance metabolic health in T2DM.Keywords: anaerobic, metabolic inflammation, adipokines, complementary treatment